Minority rights and minority protection in Europe - Agarin, Timofey; Cordell, Karl, 1956- (Rowman & Littlefield International Ltd, 2016)
Assesses the nature of minority rights protection in post-communist Europe and evaluates the impact of domestic institutions on the operation of the European Minority Rights Regime.